Controlling London's Growth : Planning the Great Wen, 1940 - 1960. - Foley, Donald L. (UC Press voices revived., 2022)
The story recounted here--that of efforts in recent years to plan for Greater London--is both unique and important. It concerns a world metropolis that, faced with an urgent need to rebuild its war-damaged central areas while still at war, prepared a notable set of special plans. And it describes subsequent vigorous efforts to carry these plans into effect. The London record is singularly impressive, unmatched by metropolitan planning efforts elsewhere. It has.